Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation (GI) untuk Meningkatkan Hasil Belajar Siswa pada materi Himpunan pada siswa Kelas VII SMP Negeri 5 Kota Ternate - Hujairah Hi Muhammad (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to determine: (i) How are the student learning outcomes on the set material using group investigation type cooperative learning? (ii) Can using the group investigation type cooperative learning improve student learning outcomes on set material?. This research is a classroom action research conducted in two cycles, with the subject of the research being 25 students of class VII1 SMP Negeri 5 Ternate City. Data analysis used the 5 scale benchmark (PAP) and the value of gain. Based on the results of the study, it can be concluded that: (i) the learning outcomes of Class VII1 students of SMP Negeri 5 Ternate City in studying the set material increased after the action was taken, namely the initial test 22 students (88.0%) failed qualifications, 1 student (4.00%) ) good qualification, 1 student (4.00%) has sufficient qualification, 1 student (4.00%) has less qualification, and in the initial test there are no students who get special qualifications. Cycle I, 12 students (48.0%) failed qualifications, 4 students (16.0%) had good qualifications, 2 students (8.00%) had sufficient qualifications, 7 students (28.0%) had poor qualifications. In the second cycle, 6 students (24.0%) had special qualifications, 14 students (56.0%) had good qualifications, 5 students (20.0%) had sufficient qualifications. (ii) Student learning outcomes in the first cycle were 0.46% in the medium category, and in the second cycle it was 0.77% in the high category. So the use of cooperative learning type (GI) can improve the learning outcomes of Class VII students of SMP Negeri 5 Ternate City.